Probiotics as Beneficial Dietary Supplements to Prevent and Treat Cardiovascular Diseases: Uncovering Their Impact on Oxidative Stress - Vasquez, Elisardo C. (Oxid Med Cell Longev, 2019)
The gut microbiota, the ecosystem formed by a wide symbiotic community of nonpathogenic microorganisms that are present in the distal part of the human gut, plays a prominent role in the normal physiology of the organism. The gut microbiota's imbalance, gut dysbiosis, is directly related to the origin of various processes of acute or chronic dysfunction in the host. Therefore, the ability to intervene in the gut microbiota is now emerging as a possible tactic for therapeutic intervention in various diseases. From this perspective, evidence is growing that a functional dietary intervention with probiotics, which maintain or restore beneficial bacteria of the digestive tract, represents a promising therapeutic strategy for interventions in cardiovascular diseases and also reduces the risk of their occurrence. In the present work, we review the importance of maintaining the balance of the intestinal microbiota to prevent or combat such processes as arterial hypertension or endothelial dysfunction, which underlie many cardiovascular disorders. We also review how the consumption of probiotics can improve autonomic control of cardiovascular function and provide beneficial effects in patients with heart failure. Among the known effects of probiotics is their ability to decrease the generation of reactive oxygen species and, therefore, reduce oxidative stress. Therefore, in this review, we specifically focus on this antioxidant capacity and its relationship with the beneficial cardiovascular effects described for probiotics.